2015
DOI: 10.1007/s11120-015-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of nutrient media composition for hydrogen production in Chlamydomonas

Abstract: Microalgae are capable of biological H2 photoproduction from water, solar energy, and a variety of organic substrates. Acclimation responses to different nutrient regimes finely control photosynthetic activity and can influence H2 production. Hence, nutrient stresses are an interesting scenario to study H2 production in photosynthetic organisms. In this review, we mainly focus on the H2-production mechanisms in Chlamydomonas reinhardtii and the physiological relevance of the nutrient media composition when pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 122 publications
0
14
0
1
Order By: Relevance
“…S deprivation is a strategy widely used to enhance photobiological-H 2 production in Chlamydomonas [ 35 , 36 ], which can lead to the highest H 2 yields ( Table 1 ). However, this strategy has several drawbacks, including growth inhibition and the loss of the cell viability (caused by the S prolonged deficiency), which reduce the potential for H 2 generation.…”
Section: Characteristics Of the Algae–bacteria Association For H mentioning
confidence: 99%
See 1 more Smart Citation
“…S deprivation is a strategy widely used to enhance photobiological-H 2 production in Chlamydomonas [ 35 , 36 ], which can lead to the highest H 2 yields ( Table 1 ). However, this strategy has several drawbacks, including growth inhibition and the loss of the cell viability (caused by the S prolonged deficiency), which reduce the potential for H 2 generation.…”
Section: Characteristics Of the Algae–bacteria Association For H mentioning
confidence: 99%
“…Different culturing approaches have also been developed to alleviate the identified bottlenecks. Among these approaches are the modulation of the light intensity [ 14 , 27 , 28 , 29 , 30 , 31 ], the optimization of the photosynthetic electrons flow towards the HYDAs [ 29 , 32 , 33 , 34 ], the implementation of nutrient stresses, especially sulfur (S) deprivation, influencing H 2 production [ 35 , 36 , 37 , 38 , 39 ], the addition of O 2 scavengers into the culture media [ 33 , 40 , 41 ], or cell immobilization [ 42 , 43 , 44 ]. Moreover, in recent years, the co-cultivation of alga and bacteria has arisen as an alternative strategy to increase algal H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…PFR activity is coupled to FDX1, which accepts the electrons from the catalyzed reaction and donates them to HYDA1. It has been shown that PFR is also able to use, in addition to pyruvate, oxaloacetate as a substrate (reviewed in [1]).…”
Section: Introductionmentioning
confidence: 99%
“…Mixotrophic and autotrophic growth conditions refer to the presence or absence of acetate, respectively. Importantly, most studies about H 2 production in Chlamydomonas have been done using Tris-Acetate-Phosphate (TAP) medium, and it is well known that acetate strongly enhances H 2 production in Chlamydomonas (reviewed in [1]).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1940s, Hans Gaffron and his group observed that Chlamydomonas reinhardtii had the ability to produce hydrogen under anaerobic conditions (Gaffron and Rubin 1942 ). The production of hydrogen from water and sunlight using microalgae has been the subject of applied research since the early 1970s (Benemann 1996 ), but since the discovery of hydrogen production by sulfur deprivation (Ghirardi et al 2000 ; Melis et al 2000 ), which allowed a significant amount of hydrogen to be produced from light by biophotolysis, this research has advanced substantially (Burgess et al 2011 ; Eroglu and Melis 2011 ; Dubini and Ghirardi 2015 ; Gonzalez-Ballester et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%